40=x(x+3)

Simple and best practice solution for 40=x(x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 40=x(x+3) equation:


Simplifying
40 = x(x + 3)

Reorder the terms:
40 = x(3 + x)
40 = (3 * x + x * x)
40 = (3x + x2)

Solving
40 = 3x + x2

Solving for variable 'x'.

Reorder the terms:
40 + -3x + -1x2 = 3x + -3x + x2 + -1x2

Combine like terms: 3x + -3x = 0
40 + -3x + -1x2 = 0 + x2 + -1x2
40 + -3x + -1x2 = x2 + -1x2

Combine like terms: x2 + -1x2 = 0
40 + -3x + -1x2 = 0

Factor a trinomial.
(5 + -1x)(8 + x) = 0

Subproblem 1

Set the factor '(5 + -1x)' equal to zero and attempt to solve: Simplifying 5 + -1x = 0 Solving 5 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -1x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -1x = 0 + -5 -1x = 0 + -5 Combine like terms: 0 + -5 = -5 -1x = -5 Divide each side by '-1'. x = 5 Simplifying x = 5

Subproblem 2

Set the factor '(8 + x)' equal to zero and attempt to solve: Simplifying 8 + x = 0 Solving 8 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + x = 0 + -8 Combine like terms: 8 + -8 = 0 0 + x = 0 + -8 x = 0 + -8 Combine like terms: 0 + -8 = -8 x = -8 Simplifying x = -8

Solution

x = {5, -8}

See similar equations:

| 2x+x/2+x+20=580 | | (5w+1)(2-w)=0 | | (1.5*b)*b=0 | | 1.5b*b=0 | | X*2=-9x-8 | | 3x-5-2x=5-12 | | 0.5(4x-2)= | | (5x-90)=2x+30 | | C-6c=0 | | (11r+6)(5r-4)=0 | | Y=0.6(100)+b | | 6n^2/2 | | x+13=5x | | 5(x)=5(2x-3) | | R=b^2+1 | | (5x)2=15x-45 | | 3c-1=c | | 3x-5-x=2x-3 | | 3ysquared= | | 3(2x+1)-2(3-2)=13 | | 15x-45/2=5x | | 1/3x3/8 | | (7a)x(2b)=0 | | 15/105 | | 9z+4-5z-5= | | -6(r-7)=-54 | | 8+9a=7 | | 4x+3+2y=11 | | 7x-4.23=0.2+2.57 | | 7x-4.23=0.2 | | -8(n-2)-2=-21-3n | | 3x=2(7x-3) |

Equations solver categories